Análise econômica financeira das alianças estratégicas entre as empresas concorrentes do tipo pseudo-concentração: o caso da aliança entre TAM e VARIG - Lucini, Juliana (Universidade do Vale do Rio do Sinos, 2006)
The structure and the strategy of the organizations have being affected by the international competition intensified in the last decades. Because of this concurrency the entities have being searching strategies in order to remain competitive in the market being one of them to look for partnership with other companies. This is the reason that motivated the present study which general main aim is to verify the reflexes of strategic alliances in the economic income of the companies that adopted it, using as reference the case of TAM and VARIG during their partnership. The methodology of this present study is classified as for the technical proceedings like “documental” therefore financial statements of VARIG and TAM are used to describe possible impacts from the partaking of flights occurred from 2003 until 2005. The method of research used gave us the possibility to conclude that the strategic alliance probably influenced the reduction of operational costs and expenses of both companies during the period of tim
Keywords: aviação civil; custos operacionais; despesas operacionais; aliança estratégica; civil aviation; operational costs; operational expenses; strategic alliance; Ciências Sociais Aplicadas